Analysis of The Influence of Work Motivation, Work Environment and Salary on Employee Job Satisfaction at PT. Bank Mandiri Taspen Tbk Gatot Subroto Medan Branch Office - Melynia Amira Putri; Kholilul Kholik (Jurnal Fokus Manajemen, 2026)
This research was conducted at PT. Bank Mandiri Taspen Tbk, Gatot Subroto Branch Office, Medan. This study aimed to determine and analyze the influence of work motivation, work environment, and salary on employee job satisfaction at PT. Bank Mandiri Taspen Tbk, Gatot Subroto Branch Office, Medan. The research method used was quantitative. The population was all 57 employees at PT. Bank Mandiri Taspen Tbk, Gatot Subroto Branch Office, Medan. The sampling technique used was saturated sampling, resulting in a sample size of 57. Data collection techniques included observation, questionnaires, and documentation. Data analysis was performed using Multiple Linear Regression, Partial Tests, and Simultaneous Tests using SPSS Version 27. The results of the study indicate that partially work motivation has a positive and significant effect on employee job satisfaction with a correlation of 0.179 and t-count 1.769 > t-table 1.674 and a significance of 0.038 < 0.05. The work environment partially has a positive and significant effect on employee job satisfaction with a correlation of 0.231 and t-count 2.309 > t-table 1.674 and a significance of 0.025 < 0.05. Salary partially has a positive and significant effect on employee job satisfaction with a correlation of 0.322 and t-count 2.351 > t-table 1.674 and a significance of 0.022 < 0.05. Work motivation, work environment, and salary simultaneously have a positive and significant effect on employee job satisfaction with F-count 21.219 > F-table 2.779 and a significance of 0.000 < 0.05. Determination shows a result of 0.520, meaning that work motivation, work environment, and salary contribute to employee job satisfaction 52% of all factors that can contribute and influence employee job satisfaction at PT. Bank Mandiri Taspen Tbk Gatot Subroto Medan Branch Office.